PELATIHAN PENERAPAN PEMBELAJARAN SAINTIFIK DAN PENATAAN LINGKUNGAN UNTUK MENFASILITASI MERDEKA BELAJAR PADA GURU-GURU KB TK GUGUS 7 KASIHAN BANTUL - Titik, Titik Mulat Widyastuti; Novitasari, Khikmah; Retno Utami, Novianti (Universitas PGRI Yogyakarta, 2024)
This service is motivated by the problems faced by family planning teachers at Cluster 7 Kindergarten, Kasihan Bantul District, Yogyakarta regarding: 1). Teachers still lack understanding in implementing a scientific approach in learning at school. 2). Teachers do not understand the stages of implementing scientific learning such as observing, asking questions, collecting, associating and communicating information in class activities. This service aims to provide training and assistance in the application of scientific learning and environmental management to facilitate independent learning for early childhood. The method in this research uses: lectures, questions and answers, and supervisory actions carried out over 2 cycles. There are four stages in service activities and each cycle consists of: planning, implementation, observation and evaluation (reflection). The results of the training implementation show that the PAUD teachers at KB TK Gugus 7, Kasihan Bantul District, Yogyakarta, in implementing scientific learning and environmental arrangements to facilitate independent learning for early childhood improved after participating in training and mentoring activities. Keywords: Scientific learning, environmental management, independent learning.